Localization of Tissue Fibrinolysis in the Gastrointestinal Tract - Stenberg, Björn; Risberg, Bo; Bois, Marc; Zettergren, Lennart; Peterson, Hans-Inge (Thrombosis and Haemostasis, 1979)
Tissue fibrinolysis in the stomach and intestine of the rat was studied with a histochemical technique. After perfusion of blood vessels to reduce the influence of circulating plasminogen activator and inhibitor fibrinolysis was localized mainly to submucosal arteries and to the serosa of the gastrointestinal tract. This is opposite to previous observations, in which tissue fibrinolysis in the gastrointestinal tract was suggested to be mainly localized to veins. A method for semiquantitative analysis of tissue fibrinolysis in the rat stomach is described.